MYC‐activated LINC00607 promotes hepatocellular carcinoma progression by regulating the miR‐584‐3p/ROCK1 axis. (14th February 2023) - Dong, Shuilin; Wang, Wei; Liao, Zhibin; Fan, Yawei; Wang, Qi; Zhang, Lei
Abstract: Background: There have been many reports of long non‐coding RNAs (lncRNAs) in tumors, and abnormally expressed lncRNA is closely related to hepatocellular carcinoma (HCC). The mechanism of LINC00607 in HCC has not been reported. Methods: We utilized qPCR to evaluate the RNA expression level. The mechanism of MYC binding to the LINC00607 promoter was revealed through chromatin immunoprecipitation assay and dual luciferase reporter assay. The proliferation and invasive ability were evaluated by CCK‐8 and transwell assays. The relation between LINC00607 and miR‐584‐3p was assessed by RNA immunoprecipitation assay and dual luciferase reporter assay. The level of ROCK1 was evaluated by qPCR and western blot. Results: In this research, we found that the expression of LINC00607 was higher in HCC tissues when compared with that in the adjacent non‐tumor tissues. Meanwhile, MYC was observed to interact with the LINC00607 promoter, leading to the upregulation of LINC00607 in HCC. We further revealed that LINC00607 functioned as a sponge for miR‐584‐3p . Cell proliferation and migration assays showed that miR‐584‐3p may inhibit the HCC progression. Moreover, we found that the miR‐584‐3p inhibitor could reverse the effects of LINC00607 downregulation in HCC through rescue experiments. Through verification, miR‐584‐3p bound to the 3′ UTR of ROCK1 to downregulate its expression. Conclusion: LINC00607 regulated by MYC can promote the proliferation, migration and invasion of HCC cells through the miR‐584‐3p /ROCK1 axis. Abstract : In hepatocellular cancer cells, MYC was observed to interact with the LINC00607 promoter, leading to the upregulation of LINC00607 . LINC00607 functioned as a sponge for miR‐584‐3p, which negatively affected the expression of ROCK1, thus promoting the proliferation, migration and invasion of HCC cells.